Outcome of manipulation under anesthesia with or without intra-articular steroid injection for treating frozen shoulder: A retrospective cohort study. Issue 13 (2nd April 2021) - Song, Chengjun; Song, Chengwei; Li, Chengwen
Abstract : Abstract: Manipulation under anesthesia (MUA) combined with intra-articular steroid injection (ISI) is preferred in management of the refractory frozen shoulder (FS). This study aimed to evaluate the effect of MUA with ISI or not on pain severity and function of the shoulder. Data on 141 patients receiving MUA with primary FS refractory to conservative treatments for at least 1 month were retrospectively obtained from medical records. We performed propensity score matching analysis between patients receiving MUA only and those receiving MUA plus ISI, and then conducted logistic regression analysis to identify the risk factors for the need to other treatments during 6-month follow-up. More improvement in terms of the SPADI pain scores and passive ROM at 2 weeks after first intervention remained in patients receiving MUA plus ISI after matching. The need to other treatments during 6-month follow-up occurred in 10.6% patients (n = 141). Logistic regression analysis revealed that a repeat MUA 1 week after first intervention was a protective factor (OR 0.042; 95% CI 0.011–0.162; P  = .000) and duration of disease was the only one risk factor (OR 1.080; 95% CI 1.020–1.144; P  = .008) for the need to other treatments during follow-up. ISI immediately following MUA provided additional benefits in rapid relief of pain and disability for patients with refractory FS. Pain and disability of the shoulder may be rapidly alleviated by an earlier MUA from the onset of the symptoms and a repeat MUA 1 week after first intervention.